Agency shifts in agricultural land governance and their implications for land degradation neutrality. (January 2021) - Debonne, Niels; van Vliet, Jasper; Metternicht, Graciela; Verburg, Peter
Graphical abstract: We present ways for LDN brokers to motivate or curtail value chain actors. Highlights: We report rise of contract farming, large-scale land acquisitions, and related processes. Reported dynamics all represent agency shifts in land governance towards value chain actors. Agency shifts can cause or intensify land degradation, undermining progress towards LDN. Agency shifts can also catalyze progress towards LDN using value chain instruments. Abstract: Given current land degradation trends, Land Degradation Neutrality (LDN, SDG Target 15.3) by 2030 could be difficult to attain. Solutions to avoid, reduce, and reverse land degradation are not being implemented at sufficiently large scales, pointing to land governance as the main obstacle. In this paper, we review dynamics in agricultural land governance, and the potential this may have to enable land degradation or provide solutions towards LDN. The literature reveals agency shifts are taking place, where value chain actors are given increasing decision-making power in land governance. These agency shifts are manifested in two interrelated trends: First, through agricultural value chain coordination, such as contract farming, value chain actors increasingly influence land management decisions. Second, international large-scale land acquisitions and domestic larger-scale farms, both instances of intensified direct involvement of value chain with land management, are overtaking significant areas of land. These new arrangements are associated with agricultural expansion, and are additionally associated with unsustainable land management due to absent landowners, short-term interests, and high-intensity agriculture. However, we also find that value chain actors have both the tools and business cases to catalyze LDN solutions. We discuss how governments and other LDN brokers can motivate or push private actors to deploy private governance measures to avoid, reduce, and reverse land degradation. Successful implementation of LDN requires refocusing efforts to enable and, where necessary, constrain all actors with agency over land management, including value chain actors.